2022
DOI: 10.1017/s0950268822001170
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of Orientia tsutsugamushi infection in rural South India

Abstract: Scrub typhus is a common bacterial infection in Asia caused by Orientia tsutsugamushi. This serological cohort study estimated the incidence of infection in a rural population in South India. Participants were enrolled through systematic sampling in 46 villages at baseline, and revisited the following year. Blood samples were tested for IgG antibodies using ELISA, followed by indirect immunofluorescence assays (IFA) in those positive for ELISA at both rounds. A case was defined as sero-conversion (ELISA), or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Epidemiological surveys have shown that the infection rate of H. pylori infection is related to social economic situation, living conditions, sanitary conditions and living habits, occupation and quality of drinking water ( Xu Wenting and Chengfu, 2022 ). The prevalence of scrub typhus is also found in specific populations (e.g., military personnel or plantation workers) and agricultural staff in townships ( Devamani et al, 2022 ). To avoid any influence of environmental and occupational factors on the study results, we strictly matched the regional distribution, age, and gender of the Tsutsugamushi patients and the healthy medical examination population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological surveys have shown that the infection rate of H. pylori infection is related to social economic situation, living conditions, sanitary conditions and living habits, occupation and quality of drinking water ( Xu Wenting and Chengfu, 2022 ). The prevalence of scrub typhus is also found in specific populations (e.g., military personnel or plantation workers) and agricultural staff in townships ( Devamani et al, 2022 ). To avoid any influence of environmental and occupational factors on the study results, we strictly matched the regional distribution, age, and gender of the Tsutsugamushi patients and the healthy medical examination population.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Orientia tsutsugamushi in humans can manifest with a wide range of clinical symptoms, varying from mild (asymptomatic) to severe and potentially life-threatening conditions ( Park et al, 2021 ; Devamani et al, 2022 ). The underlying mechanisms for these variations are not fully understood, but it was believed that factors such as the strain of Orientia tsutsugamushi and the immune status of the host may play a role ( Elliott et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%